1993
DOI: 10.1080/01652176.1993.9694397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of litter size and breed on variation in length of gestation in the dog

Abstract: SUMMARYThe variation in the length of gestation, the period from mating until parturition, was studied in 77 dogs of different breeds; the time for mating was determined by measuring peripheral blood progesterone levels. The mean length of gestation was 62.1 ± 0.2 (S.E.M.) days, with a variation of 11 days. The number of pups appeared to influence the length of gestation. Length of gestation was negatively correlated (r = -0.96, P < 0.001, n = 44) with litter size in litters with 7 or fewer pups. The intra-bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
2
9

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 5 publications
(2 reference statements)
7
78
2
9
Order By: Relevance
“…1). Okkens et al (2001) reported that the number of fetuses and t h e duration of gestation were negatively correlated. In contrast, there was no corrrelation in the present study agreed with the observations of Kutzler et al (2003).…”
Section: Resultsmentioning
confidence: 99%
“…1). Okkens et al (2001) reported that the number of fetuses and t h e duration of gestation were negatively correlated. In contrast, there was no corrrelation in the present study agreed with the observations of Kutzler et al (2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, results published in various studies are inconsistent (Gavrilovic et al 2008;Borge et al 2011), possibly because they are based on reproductive efficiency data sets of bitches pertaining to various breeds (Bouchard et al 1991;Okkens et al 2001;Eilts et al 2005;Chatdarong et al 2007;Ortega-Pacheeo et al 2007;Borge et al 2011) and only very few studies deal with reproductive efficiency of only one dog breed, more specifically Drever (Gavrilovic et al 2008), Irish hounds (Urfer 2009), German Shepherds (Mutembei et al 2002), Beagles (Shimatsu et al 2007), Boxers (Forsberg and Persson 2007), and English bulldog breed (Wydooghe et al 2013). Moreover, results of some studies are only based on data from a questionnaire (Mutembei et al 2002;Forsberg and Persson 2007;Wydooghe et al 2013) and there is no information (or no rigorous information) about reproductive management of the breeders concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing litter size are for example season of the year, number of previous litters (Gavrilovic et al 2008), age of parents (Borge et al 2011), and breed (Okkens et al 2001;Borge et al 2011). However, results published in various studies are inconsistent (Gavrilovic et al 2008;Borge et al 2011), possibly because they are based on reproductive efficiency data sets of bitches pertaining to various breeds (Bouchard et al 1991;Okkens et al 2001;Eilts et al 2005;Chatdarong et al 2007;Ortega-Pacheeo et al 2007;Borge et al 2011) and only very few studies deal with reproductive efficiency of only one dog breed, more specifically Drever (Gavrilovic et al 2008), Irish hounds (Urfer 2009), German Shepherds (Mutembei et al 2002), Beagles (Shimatsu et al 2007), Boxers (Forsberg and Persson 2007), and English bulldog breed (Wydooghe et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The interval is highly variable (2-10 months) among the breeds (3,4). Various factors that affect the interestrous period and pregnancy duration, such as breed, age, parity, and litter size have been described in previous studies (3,5,6).Although bitches are considered nonseasonal, the seasonal effect on the reproductive parameters are still contradictory. Studies confirming (1,7,8) and denying (3,9-11) seasonal effects on bitch reproduction are available.…”
mentioning
confidence: 99%